Halal Guarantee System for Bottled Drinking Water (AMDK) Production of Al-Falah Bangakalan Copontren in View of Has 23000 - Azzah Rahmalia Nabilah; Muttaqin Choiri; Muhammad Ersya Faraby (Penerbit Hellow Pustaka, 2024)
The need for halal products is very urgent at the moment, especially regarding Muslim consumers in Indonesia. In an effort to improve the Islamic boarding school economy, the government launched the